background image

16.3. BEFORE THE DIAGRAM

261

and thus

P

Q

up

f

.

Let

A

,

B

be filters on Γ. Let

d

FCD

up

A

=

d

FCD

up

B

. We need to prove

A

=

B

.

(The rest follows from proof of the lemma

924

). We have:

A

=

FCD

l

X

×

Y

X

×

B

up

A

X

P

A, Y

P

B

=

FCD

l

X

×

Y

X

×

B

X

P

A, Y

P

B,

P

up

A

:

P

X

×

Y

X

×

B

=

FCD

l

X

×

Y

X

×

B

X

P

A, Y

P

B,

P

up

A

:

h

P

i

X

Y

= (*)

FCD

l

X

×

Y

X

×

B

X

P

A, Y

P

B,

d

n

h

P

i

X

X

up

A

o

v

Y

=

FCD

l

X

×

Y

X

×

B

X

P

A, Y

P

B,

d

n

h

P

i

X

X

up

d

RLD

up

A

o

v

Y

=

FCD

l

X

×

Y

X

×

B

X

P

A, Y

P

B,

D

(

FCD

)

d

RLD

up

A

E

X

v

Y

= (**)

FCD

l

X

×

Y

X

×

B

X

P

A, Y

P

B,

D

d

FCD

up

d

RLD

up

A

E

X

v

Y

=

FCD

l

X

×

Y

X

×

B

X

P

A, Y

P

B,

D

d

FCD

up

A

E

X

v

Y

.

(*) by properties of generalized filter bases, because

n

h

P

i

X

P

up

A

o

is a filter base.

(**) by theorem

1066

.

Similarly

B

=

FCD

l

X

×

Y

X

×

B

X

P

A, Y

P

B,

D

d

FCD

up

B

E

X

v

Y

.

Thus

A

=

B

.

Proposition

1388

.

g

f

Γ(

A, C

) if

f

Γ(

A, B

) and

g

Γ(

B, C

) for some

sets

A

,

B

,

C

.

Proof.

Because composition of Cartesian products is a Cartesian product.

Definition

1389

.

g

f

=

d

F

Γ(

A,C

)

n

G

F

F

up

f,G

up

g

o

for

f

F

Γ(

A, B

) and

g

F

Γ(

B, C

) (for every sets

A

,

B

,

C

).

We define

f

1

for

f

F

Γ(

A, B

) similarly to

f

1

for reloids and similarly derive

the formulas:

1

. (

f

1

)

1

=

f

;

2

. (

g

f

)

1

=

f

1

g

1

.